2008
DOI: 10.1167/iovs.07-1081
|View full text |Cite
|
Sign up to set email alerts
|

Release of Membrane-Associated Mucins from Ocular Surface Epithelia

Abstract: Results suggest that the extracellular domains of MUC1, MUC4, and MUC16 can be released from the ocular surface by agents in tears. Neutrophil elastase and TNF, present in higher amounts in the tears of patients with dry eye, may cause MAM release, allowing rose bengal staining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
75
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 40 publications
5
75
0
Order By: Relevance
“…39,52 MMP-7 has been reported to cleave MUC16, the principal mucin constituent of the cornea epithelial glycocalyx, from cultured human cornea epithelial cell membranes. 40 Taken together, these findings implicate MMPs in the disruption of molecules maintaining para-and transcellular cornea barrier.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…39,52 MMP-7 has been reported to cleave MUC16, the principal mucin constituent of the cornea epithelial glycocalyx, from cultured human cornea epithelial cell membranes. 40 Taken together, these findings implicate MMPs in the disruption of molecules maintaining para-and transcellular cornea barrier.…”
mentioning
confidence: 81%
“…[38][39][40] Gelatinases have been implicated in physiologic desquamation of the cornea epithelium. Decreased corneal epithelial desquamation in vitamin A-deficient rats was associated with significantly decreased MMP-2 and -9 expression.…”
mentioning
confidence: 99%
“…The triggers and mechanisms involved in release of the ectodomain are only partially understood. It has been hypothesized that mucin extracellular domains are released in response to mechanical force, interactions with microbes or alteration in pH, ionic concentration, hydration [4] or inflammatory stimuli such as TNFα and neutrophil elastase [29]. At the mucosal surface, the shed domains might function as decoy receptors for pathogens.…”
Section: General Features Of Transmembrane Mucinsmentioning
confidence: 99%
“…MUC16 can be cleaved between the N-and C-terminal fragments, possibly in the SEA (sea urchin sperm protein, enterokinase, and agrin) domain, with potential influence on immunoreactivity, since both epitopes for OC125 and M11-like antibodies contain parts of two consecutive SEA domains with a linker (Maeda et al, 2004;Blalock et al, 2008). So far, proteomic profiling identified a 2351.2 kDa protein/spot as high molecular mass MUC16/CA125 (Milardi et al, 2012), but a CA125-immunoreactive band at 130 kDa was also observed in another immunoblot study (Halila, 1985).…”
Section: Discussionmentioning
confidence: 99%